Education and training to build awareness of organizational diversity in senior high school teachers - Hana Panggabean; Juliana Murniati (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Diversity in educational settings exposes all involved actors to issues related to inherent (e.g. age, gender) and acquired diversity (e.g., education, marital status). This 400-hour program is aimed at building diversity awareness for high school teachers indicated by a good comprehension of diversity issues, create favorable learning atmosphere, and augmenting learning motivation.  Mixing asynchronous and synchronous techniques, activities are carried out through Zoom lectures, group discussions, role play, and project assignments. At the end of the training program, participants are expected to complete an individual project within three weeks’ time. A baseline survey was conducted as well as post-tests, questionnaires, and personal journals that would allow a comprehensive view of the program’s performance. Based on the evaluations, the program has contributed to a favorable learning atmosphere and learning motivation. Furthermore, participants’ diversity awareness was developed along with their attitude and behavioral change in dealing with school diversity. A short and moderate learning effect was acquired. It is our recommendation that the school management sustains the learning effect by promoting a school climate of openness, tolerance, and respect.